Knowledge, attitude and practices of hookah smoking among medical students in Gujarat, India: a cross sectional study - Rami, Kiran; Makvana, Bhikhu J.; Thakor, Nilesh Chandradityasinh (International Journal of Advances in Medicine, 2017)
Background: Tobacco is a preventable cause of morbidity and mortality across the world. Tobacco is used in different forms and among these hookah smoking is gaining immense popularity mainly because of youth appeal. Very few studies have been conducted to determine general smoking pattern and smoking habits among medical students. Objective of the study was to assess knowledge, attitude and practices of hookah smoking among medical students. Methods: A cross-sectional study was conducted among medical students of AMC MET Medical College, Ahmedabad, Gujarat, India during April 2012 to August 2012. A simple random sampling technique was used. Inclusion criteria included all the students from MBBS program. Total 200 students from year one until year five was selected to participate in this study. Students were briefed about the topic of the study before the distribution of questionnaires. Predesigned, pretested and semi structured proforma was used to collect information regarding hookah smoking. The confidentiality of the study participants was ensured and informed consent was obtained. The study was approved by the ethics committee of the institute. The obtained data was analyzed using SPSS version 17 (Trial version). Results: Out of 200 students, 21 (10.5%) the medical students smoke hookah. Average age of starting hookah smoking was 17.4 years. 38.1% of smokers preferred cigarette over hookah. 93.3% of the non-Smokers considered hookah smoking as injurious to health. Friends of the hookah smokers (peer pressure) were responsible for starting of hookah smoking in majority of the hookah smokers (85.7%). Out of 21 medical students who smoke hookah, only 5 students had tried to quit hookah. Conclusions: Our study reveals the alarming situation of high practice of hookah smoking among medical students and thus that active measures should be taken to control this current condition especially among students by increasing awareness in them with the hazardous side effects of hookah smoking.